An Assessment of the Suitability of Scour Estimation Methodologies for a Northern Ireland Scour Risk Assessment - O'Higgins, Connor; ICASP14; Campbell, Kristopher; Braiden, Pearce; Lydon, Myra (My University, 2023)
Scour risk estimation is a complex discipline given the inherent natural variability of watercourses and bed materials. The majority of risk assessments are based initially on qualitative measures followed by the estimation of maximum(equilibrium) scour depth using semi-empirical equations. The semi-empirical methods are limited by the flume conditions and associated limited scale they were developed in and the bed material that they simulated. Most methods are derived from flume testing using uniform quartz sands. When compared to reality most empirical relationships are known to over-predict scour by considerable margins. Scour is a dynamic natural phenomenon that is well documented, however globally there is a lack of industry ready tools for the network wide assessment of scour and there is currently no framework for scour risk assessment in Northern Ireland. The principal objective of this research is to provide an objective view on existing scour risk assessment methodologies with the intention of providing an easily practicable method of estimating scour risk that represents scour processes well in the context of Northern Ireland. The research will document the application and results of various existing methodologies on three Northern Irish bridges. The analysis section of this research will focus on analyzing the criticality of the parameters associated with scour assessment to ascertain which parameters should be of primary concern to asset managers.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED